THE ROLE OF HOME READING CLASS IN THE LANGUAGE TRAINING OF STUDENTS OF INTERNATIONAL ECONOMIC RELATIONS - M. V. Grineva (Vestnik MGIMO-Universiteta)
Nowadays the growing professional orientation of all the aspects of foreign language teaching is widely recognized as the main trend in the process of enhancing the system of foreign language teaching at higher education institutions which specialize in training students majoring in international economic and political relations. In view of the above the article focuses on the role of teaching home reading and analyzes the possibility of its integration into the professionally oriented process of teaching English as a foreign language to would-be economists. Another reason why the issue of teaching home reading is of utmost importance is that due to the prevailing communicative approach in teaching English as a foreign language, coupled with teaching English for professional purposes, some researchers and practising teachers are of the opinion that large-sized literary works are «incompatible» with an efficient foreign language curriculum. Hence, the importance of analyzing the role of such texts in teaching English given its increasing professionalization. According to the author, the specific features of reading literature in a foreign language make it an irreplaceable and useful resource for a wide range of linguistic competences. However, its competence forming potential can only be fully realized if certain general and specifically professional criteria for choosing a literary text for a home reading class are implemented. Such criteria are as follows: the reader’s emotional involvement with the plot and the problems raised in a book; a low degree of linguistic and cultural deviations; popular literary genres; clear professional orientation of a text. The author goes on to analyze the professionally oriented novels by J.Grisham and J.Mead and concludes that they can be successfully incorporated into professionally oriented process of teaching English, as they fully satisfy all the above criteria and, moreover, represent a unique resource for a wide spectrum of professional competences of a future economist, both linguistic and non-linguistic (e.g. sociocultural and analytical competences). In addition, the learning aids written by the author encourage students to treat the text of the books as a source of professionally meaningful information.